PENGARUH MOTIVASI KERJA DAN PEMBERIAN TUNJANGAN KINERJA TERHADAP KINERJA PEGAWAI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN LAMPUNG UTARA - Pebriyadi Pebriyadi (SIMPLEX: Journal of Economic Management, 2020)
The aim of this research were to determine The Effect of Work Motivation and Performance Allowances on Employee Performance. This type of research using quantitative approaches and data collection techniques using questionnaires and observations. The population in this study were employees who worked at BPKAD of North Lampung Regency and were taken by purposive sampling using Slovin formula to 86 respondents. Findings signify that: (1) Does work motivation significantly influence employee performance? (2) does the provision of performance allowances have a significant effect on employee performance? (3) does motivation and performance allowance have a significant effect on employee performance